Acute Transverse Myelitis: Demyelinating, Inflammatory, and Infectious Myelopathies - West, Timothy W.; Hess, Christopher; Cree, Bruce A. C. (Seminars in Neurology, 2012)
Acute transverse myelitis is a rare neurologic condition that has an estimated incidence of up to 3 per 100,000 patient years (0.003%). Although rare, acute transverse myelitis can have devastating neurologic effects with up to two-thirds of patients having a moderate to severe degree of residual disability. The term acute transverse myelitis was previously reserved for idiopathic cases, but currently is used to encompass the general clinical syndrome, whether or not the cause is known. Once adequate neuroimaging has ruled out a compressive etiology, and a lumbar puncture has demonstrated signs of inflammation within the cerebrospinal fluid, a workup of causes for an acute transverse myelitis must be undertaken. Determining the etiology of transverse myelitis can be challenging because there are autoimmune, inflammatory, and infectious diseases associated with acute transverse myelitis. The authors discuss an approach to acute transverse myelitis including clinical symptoms, neuroimaging, and biomarkers that may aid the clinician in diagnosis.
Keywords: myelitis; myelopathy; demyelinating; inflammatory